EVALUATING THE SOCIAL OPTIMALITY OF DURABLE PUBLIC GOOD PROVISION USING THE HOUSING PRICE RESPONSE TO PUBLIC INVESTMENT. (3rd February 2017) - Coate, Stephen; Ma, Yanlei
Abstract : Recent empirical work in public finance uses the housing price response to public investment to assess the efficiency of local durable public good provision. This article explores the theoretical justification for this technique. It points out that the logic justifying the technique for evaluating nondurable public good provision does not translate to the durable case. A model in which investment is determined by the interaction between a budget‐maximizing bureaucrat and a community's residents is used to demonstrate that the technique can falsely predict underprovision, falsely predict overprovision, or perform without error.